Analisis Penerapan Manajemen Risiko Operasional pada Usaha Mikro Kecil dan Menengah Sektor Kuliner ; Studi Kasus Ayam Bersih Berkah - Aulia Rahadatulaisyi; Khairunnisa Amalina; Mutia Damayanti; Asep Suwarna (Indo Publishing, 2026)
This study aims to analyze the implementation of risk management in Ayam Bersih Berkah (ABB) as a Micro, Small, and Medium Enterprise (MSME) operating in the culinary sector. This study uses a qualitative descriptive approach with data collection techniques through direct observation and interviews with Ayam Bersih Berkah outlet managers. The results of the study indicate that ABB faces various operational risks stemming from several main aspects, namely human resource risks, availability and quality of raw materials, cleanliness and quality of business premises, marketing activities, and risks related to customers. In carrying out daily operations, ABB has implemented standard operating procedures (SOPs), including storing raw chicken in the freezer, a twenty-four-hour thawing process, and a thirteen-minute frying process to maintain product quality and hygiene. In addition, ABB also implements employee performance monitoring to maintain service consistency. However, the implementation of risk management at ABB is still informal and has not been systematically documented in the form of a written policy. Risk control is carried out practically through direct supervision by outlet leaders, coordination between branches, and the use of digital systems to support operational and promotional activities. The implementation of these risk controls helps ABB maintain operational smoothness, service quality, customer satisfaction, and business sustainability in the face of competition.